2006
DOI: 10.1115/1.2717242
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Individual Single-Wall Carbon Nanotubes

Abstract: Despite the significant amount of research on carbon nanotubes, the thermal conductivity of individual single-wall carbon nanotubes has not been well established. To date only a few groups have reported experimental data for these molecules. Existing molecular dynamics simulation results range from several hundred to 6600 W/m K and existing theoretical predictions range from several dozens to 9500 W/m K. To clarify the severalorder-of-magnitude discrepancy in the literature, this paper utilizes molecular dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
186
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(210 citation statements)
references
References 41 publications
22
186
2
Order By: Relevance
“…Carbon nanotubes were once thought to also possibly exhibit divergence, but calculations performed by Mingo and Broido 29,33 as well as other molecular dynamics (MD) studies [34][35][36][37] confirmed that the thermal conductivity is large but still finite (non-divergent). However, for polymer chains, Henry and Chen 23 discovered that even in a realistic model for the interactions between atoms in a polyethylene (PE) chain, it is possible to observe divergent thermal conductivity.…”
Section: Divergent Thermal Conductivity In Polymer Chainsmentioning
confidence: 99%
“…Carbon nanotubes were once thought to also possibly exhibit divergence, but calculations performed by Mingo and Broido 29,33 as well as other molecular dynamics (MD) studies [34][35][36][37] confirmed that the thermal conductivity is large but still finite (non-divergent). However, for polymer chains, Henry and Chen 23 discovered that even in a realistic model for the interactions between atoms in a polyethylene (PE) chain, it is possible to observe divergent thermal conductivity.…”
Section: Divergent Thermal Conductivity In Polymer Chainsmentioning
confidence: 99%
“…23,27 We note that the systems investigated here are longer than the 10 to 400-nmlong systems typically investigated using MD simulation, as summarized by Mingo and Briodo 21 and Lukes and Zhong. 25 The number of carbon atoms in the CNT ranges from 29,232 ͑for the 200-nm-long, 0.83-nm-diameter CNT͒ to 195,120 ͑for the 1200-nm-long, 1.10-nm-diameter CNT͒ and the equilibrium nearest-neighbor distance is 1.42 Å. 28 Interactions between carbon atoms are modeled using the secondgeneration REBO potential 29 and interactions between water molecules are modeled using the TIP4P/2005 potential.…”
Section: Simulation Setupmentioning
confidence: 99%
“…1, we define the cross-sectional area of the CNTs to be A c = db, where b͑=0.34 nm͒ is the van der Waals thickness of the CNT surface and d is the CNT diameter. 23,25,26 We fix one layer of carbon atoms at the ends of the CNT to prevent atoms from sublimating. For graphene, we define the cross-sectional area to be A c = wb, where w is the width of the sheet ͑see Fig.…”
Section: Simulation Setupmentioning
confidence: 99%
“…and are dependent on factors such as chirality, potential, and boundary conditions (Berber et al 2000;Osman and Srivastava 2001;Padgett and Brenner 2004;Lukes and Zhong 2007;Cao and Qu 2012). In addition to these factors, Mingo and Broido (2005) suggested that the calculated thermal conductivity for single-walled nanotubes depends strongly on length, and this theory was subsequently confirmed by the experimental measurement and analytical model of Pop et al (2006).…”
Section: Thermal Conductivity Of Carbon Nanotubesmentioning
confidence: 54%